Main Factor Contribution in Factorial Screening for Ferulic Acid Production from Fibre-Pressed Oil Palm Frond (FPOPF) Using Mixed Culture - Nurul Atikah, Mohd Rodzri; Zulsyazwan, Ahmad Khushairi; Wan Mohd Hafizuddin, Wan Yussof; N., Zainol; Rozaimi, Abu Samah (Universiti Malaysia Pahang, 2015)
Ferulic acid (FA) was produced from fiber-pressed oil palm frond (FPOPF) hydrolysis using mixed culture. The mixed culture was prepared by acclimatizing FPOPF substrate with the soil from palm oil plantation for 30 days. The substrate was prepared with a ratio of 1:10 (FPOPF:water). With the aid of Design Expert 7.1, a two-level fractional factorial analysis with five factors was selected for the screening process, with a total of 16 runs overall. The five factors controlled were temperature (26°C and 40°C), pH value (5 and 9), agitation speed (0 and 150 rpm), inoculum percentage (2% and 10%) and incubation period (1 and 3 days). The ANOVA indicated that the model was significant with a determination coefficient value of 0.8978, with temperature and pH values gave highest contribution to the process. The highest FA yield obtained through out the experiments was estimated to be approximately 130 mg FA/kg FPOPF.